Sistem Informasi untuk Transaksi dan Analisis Inventori - Damayanti, Cynthia; Mustafid, Mustafid; Sarwoko, Eko Adi (JSINBIS (Jurnal Sistem Informasi Bisnis), 2011)
This research aim to developed an inventory information system which integrated convensional data records with an analysis system based on inventory theories to answer questions about supplying stock, i.e. the latest inventory counts, prediction of future sales, when to order supply and how much to order these supply. In this research, purchasing and selling data records that usually seperated, had been integrated into an inventory database so up to date inventory list can be shown at demand. Furthermore, with data of past time sales, system will predict future sales using Least Square Linear Regretion method and Moving Average method. Inventory analysis will determine the Economic Order Quantity and Reorder Cycles for single item and multi item. An early warning also will notify user when an item reach the reorder point. This information system software that can be used to answer similar inventory problems in retail or warehouse company. As addition, research shown that sales with increasing/decreasing pattern had a more accurate prediction using Linear Regretion, while Moving Averages are better for stable sales. Research also shown multi items order collectively for the same supplyer more cost beneficial rather than single item orders.